Perancangan Desain User Interface Pada Sistem Registrasi Pasien Di Rumah Sakit Graha Husada - Putri, Siti Yuliana; santi, nirma ceisa; Rokhim, Auliyaur (Al-Mantiq, 2025)
Technology is currently a tool for society, especially in public services, one of these public services is in the health sector. In the health sector, several health services such as clinics, hospitals and other health facilities have implemented technology to support their operational activities. Currently, many hospitals use computer-based systems to identify patients. One of them is a registration information system that makes services more efficient and effective. This research aims to design a user interface for a website-based patient registration system using the Design Thinking method. The result of this research is a prototype design. The second stage above is applied to the prototype stage which is used as an example of the Ul display for the hospital patient registration application that will be developed. Based on Usability Testing using Google from and distributing online questionnaires. Of the 11 respondents testing the admin and user sections, the results from the respondents were 90%, These results indicate that almost all users are satisfied with the prototype design and the results of these respondents state that the patient registration website prototype is easy to use.